Improving Students’ English Proficiency by Enhancing the Motivation through Organization Development Intervention— An Action Research Study of a Local University in China - Xue, Jianjun (ABAC ODI JOURNAL Vision. Action. Outcome, 2022)
The research aims to enhance students’ English learning motivation so as to improve their English proficiency by applying the Socio-educational Model under OD interventions. The study focuses on three dimensions of motivation, namely, attitudes to learn the language (ALL), desire to learn the language (DLL), and motivational intensity (MI). The action research was conducted in the experiment group (N=53) through three stages: pre-ODI, ODI and post-ODI. The OD interventions in the study included team meetings, appreciative inquiry workshops, CLT class, and extra-class activity. By implementing the OD interventions, data were collected both from experiment group (N=53) and control group (N=53) based on Attitude /Motivation Test Battery (AMTB) questionnaires and English proficiency test to determine the significant relationship between OD interventions and students’ language learning motivation, as well as the relationship between language learning motivation and English proficiency. The results show that OD intervention effectively enhances students’ language learning motivation and language learning motivation has significant impacts on students’ language proficiency.